PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 008 SUNGAI SEGAJAH KECAMATAN KUBU - Rokiyah '; Lazim N '; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The background of this research is theprocess of learning andteaching fourth grade 008 River State Segajah Kubu district in mathematics arestill didomonasi by the teacher so that students become passive, as well asmaterials provided by the teacher and the learning outcomes are not satisfactorywith an average value below KKM. This study aims to improve the learningoutcomes of students fourth grade math 008 River State Segajah Kubudistrict. This study was conducted on 28 students. Data were collected throughobservation using the observation sheet to the data model of learning directlythrough UH UH 1 and 2 teacher activity increased in the first cycle the firstmeeting of teachers 60% the percentage of activity, at the second meeting to 80%increased by 20%, at the first meeting of the second cycle of activity 90 increasedby 10%, while the second meeting 100% increase as much as 10%. While theactivities of the students at the first meeting of the first cycle of 55%, in the secondmeeting by 70% increased 15%, and the second cycle at the first meeting by 85%,95% the second meeting be increased by 10%.Increased student learningoutcomes in the first cycle than before tindakkan the base score of 39.3% of the 28students who completed the student and in the first cycle to 67.9% of students whocompleted 28 students and increased by 28.62, and the second cycle 85.7% ofstudents who completed 28 students, an increase of 17.8%. From the research anddiscussion as it has been described above that the use of direct instructionalmodel is correct then the activity of the teacher and student activities and studentlearning outcomes be improved and better. This information proves that thehypothesis which says: With Application of Direct Learning Model can improvethe learning outcomes of students fourth grade math 008 River State SegajahKubu district.Keywords: Direct Learning, Matemathic leaning outcome